Implementasi Metode Waterfall pada Perancangan dan Pembuatan Website Layanan Promosi Bengkel Las ALS Binjai - Jesica Siva; Supiyandi; Nova Mayasari (CV. Hawari, 2026)
This research discusses the design and creation of a promotional service website by implementing the waterfall method. The waterfall method was chosen because its linear and sequential approach is suitable for projects with clear objectives. The process begins with an analysis phase to identify features such as profile pages, service galleries, contact information, and location map integration. And design, followed by implementation using HTML, CSS, and JavaScript. Testing covers functionality and responsiveness, as well as maintenance. The result is a website that effectively promotes welding shop services. The conclusion shows that the waterfall method demonstrates a strong structure that reduces the risk of errors, although it is not flexible in terms of changes, and this website supports the digital promotion of welding shops.